2000
DOI: 10.1677/joe.0.1670039
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone induces side-branching of the ductal epithelium in the mammary glands of peripubertal mice

Abstract: Development of the functional secretory epithelium in the mammary gland of the female mouse requires the elongation of the anlage through the mammary fat pad to form the primary/secondary ductal network from which tertiary ductal side-branches and lobuloalveoli develop. In this study we examined the hormonal requirements for the spatial development of the primary/secondary epithelial network and tertiary side-branches by quantifying ductal growth and epithelial cell proliferation in normal and hormone-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 42 publications
7
74
0
2
Order By: Relevance
“…In the developing mammary gland of cycling animals, short 'tertiary' side branches of the ductal epithelium form in response to progesterone, and lobuloalveolar structures develop at the end of the tertiary branches (Atwood et al 2000, Haslam et al 2008, El Sheikh Saad et al 2011. We found striking differences in gene expression in the mammary gland between PND35 and PDN50 following exposure to V or GV, consistent with the major histological modifications observed in postpubertal mammary glands exposed to V and GV (El Sheikh Saad et al 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the developing mammary gland of cycling animals, short 'tertiary' side branches of the ductal epithelium form in response to progesterone, and lobuloalveolar structures develop at the end of the tertiary branches (Atwood et al 2000, Haslam et al 2008, El Sheikh Saad et al 2011. We found striking differences in gene expression in the mammary gland between PND35 and PDN50 following exposure to V or GV, consistent with the major histological modifications observed in postpubertal mammary glands exposed to V and GV (El Sheikh Saad et al 2011).…”
Section: Discussionsupporting
confidence: 79%
“…Estradiol (E 2 ) and GH, and their interaction with the corresponding receptors (ERa and GHR), are required for normal duct growth and morphogenesis (Daniel et al 1987, Korach et al 1996. Progesterone induces side branching of the ductal epithelium (Lydon et al 1995, Atwood et al 2000. E 2 and progesterone are required for the development of alveolar structures at each estrous cycle.…”
Section: Introductionmentioning
confidence: 99%
“…As development of the mammary gland is tightly regulated by hormones (Hovey et al, 2002), where its branching morphogenesis is regulated by P (Atwood et al, 2000), we investigated the effect of P on Msx2 gene expression. Both estrogen (E) and P treatment increased Msx2 expression in mammary glands from ovary-intact mice (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that progesterone (P) induces side-branching of the ductal epithelium in the peripubertal mouse mammary gland (Atwood et al, 2000). P receptor (PR) is critical for branching morphogenesis (Fernandez-Valdivia et al, 2005) and localizes to ductal branch points during mouse mammary development (Ismail et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When whole mount mammary glands were examined, there was defective tertiary branching and very few alveolar buds in the Pact Ϫ/Ϫ animals ( Fig. 2B), likely due to low serum progesterone and/or prolactin levels (22,23). In rodents, prolactin is the major luteotrophic hormone, released by the pituitary, that maintains the structural and functional integrity of the corpus luteum for several days after mating (24).…”
Section: Mice Lacking Pact Have Postnatal Growth and Fertility Defectsmentioning
confidence: 99%